Three cases of interesting foreign body aspiration - Fatih Meteroğlu (Dicle Medical Journal, 2014)
Foreign body aspirations cause acute fatal respiratory when they make a nearly total obstruction in trachea. Foreign bodies forwarding lower levels of tracheobronchial tree cause disruption of ventilation distal to obstruction and ease infections, depending ventilation and its infectious effects. Rigid bronchoscopy was carried out in two patients, 25 and 32 years old, who admitted to our clinic with the complaint of frequent infection and cough. Due to overlooked FBA, a bullet was removed from right lower lobe bronchus and chicken bones were removed bilaterally from lower lobes bronchi. A bead was removed from the third patient’s right main bronchus. We aimed to present three interesting cases with the literature.